Formulation Development and In-vitro Evaluation of Floating Tablets of Ciprofloxacin HCl - Venkateswarlu, Kambham (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: In the present investigation, the hydrodynamically balanced tablets of Ciprofloxacin (CPF) HCl were prepared by direct compression method. Materials and Methods: CPF HCl floating tablets were formulated using various viscosity grades of hydroxypropyl methyl cellulose (HPMC) and sodium bicarbonate as a gas generating agent. Results and Discussion: The prepared CPF HCl tablets were evaluated for weight variation, hardness, friability, drug content, tablet density, floating test, swelling index, in-vitro drug release, stability studies, and showed satisfactory results. Formulations F2, F5, F6 and F7 were showed satisfactory drug release of 91.38%, 90.66%, 94.65% and 95.10%, respectively, for 10 h and those formulations were selected for further studies. Conclusion: From the kinetic studies, it was confirmed that the drug release from its dosage forms (F2, F5, F6, and F7) follows non-Fickian diffusion. Stability studies indicated that the suitable temperature for storage of CPF HCl tablets was refrigerator temperature (2-8Â°C).